Environmental Fiqh as a Framework for Social Sustainability - Amiruddin. A; Rahmawati; Nurhaedar; Rahmi; Salmah Harun (Jurnal Lentera Insani, 2025)
When ecological crises reflect the failure of modern ethics, environmental fiqh emerges as a moral challenge to the way humans build social sustainability. The purpose of this study is to formulate and construct environmental fiqh as a framework for social sustainability in Asian Muslim communities by comprehensively explaining the relationship between fiqh norms, social practices, and ecological dynamics. This study uses a qualitative approach, combining a literature review with content analysis, and a normative-sociological approach to critically examine how environmental fiqh can be positioned as a framework for social sustainability that challenges the dominance of the secular-technocratic paradigm. The results indicate that environmental fiqh, when read critically and reconstructed progressively, has the transformative power to challenge the Asian development model based on ecological exploitation and social inequality, while offering a more equitable, long-term framework for social sustainability rooted in Islamic ethical values. By integrating environmental maqāṣid, intergenerational ethics, and revitalised fiqh concepts such as amānah, maṣlaḥah, and ḥisbah, environmental fiqh need not remain a moral discourse, but can become a normative instrument that influences public policy, corrects corporate behaviour, and strengthens civil society movements.